How Does Experience Impact Domestic Tourists’ Satisfaction? Testing the Mediating Role of Service Quality - Rahman, Muhammad Sabbir; Abdullah, Madi Bin (Indian Journal of Marketing, 2014)
The aim of the present paper was to explore the impact of tourists' experience on their satisfaction levels and examine the mediating effect of service quality in this relationship with reference to Bangladeshi domestic tourists. The study utilized a review of literature to propose a conceptual model that posits that: Tourists' experience is positively related to their overall satisfaction when service quality mediates the relationship. The model was examined in an empirical study with data from a survey conducted among 280 domestic tourists by utilizing the convenience sampling procedure from selected tourist destinations in Bangladesh. The constructs were then analyzed by using exploratory factor analysis, and validation was done through the use of confirmatory factor analysis and structural equation modeling. The findings of the study suggest that experience plays a significant role in tourists' satisfaction, while service quality plays a strong mediating role. The findings from this research provide a meaningful source of information about domestic tourists' experience and their expectations from the service providers. This paper demonstrated how service quality mediates the relationship between tourists' experience and tourists' satisfaction. To the best of our knowledge, this is the first ever and only research that has been conducted on Bangladeshi domestic tourists' perception in testing their experience and satisfaction by considering service quality as a mediating role.